2021
DOI: 10.1590/s1980-220x2020044403775
|View full text |Cite
|
Sign up to set email alerts
|

Processo de trabalho da equipe de enfermagem em Centros de Atenção Psicossocial Infanto-Juvenil

Abstract: RESUMO Objetivo Conhecer o processo de trabalho da equipe de enfermagem em Centros de Atenção Psicossocial Infanto-Juvenil de um município do estado de São Paulo. Método Estudo qualitativo, descritivo e exploratório, embasado na abordagem do materialismo histórico e dialético, realizado com a equipe de enfermagem por meio de observação participante e entrevistas semiestruturadas. Resultados Participaram 11 sujeitos da equipe de enfermagem. O processo de trabalho da equipe de enfermagem emerge da tensão d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
(39 reference statements)
0
7
0
8
Order By: Relevance
“…In all sessions, this movement was sufficient to raise a theme to be discussed and, thus, the meetings developed. Records were made immediately in a field diary, in order to avoid the loss of relevant information from the observed data, as recommended in the literature ( 17 , 18 ) .…”
Section: Methodsmentioning
confidence: 99%
“…In all sessions, this movement was sufficient to raise a theme to be discussed and, thus, the meetings developed. Records were made immediately in a field diary, in order to avoid the loss of relevant information from the observed data, as recommended in the literature ( 17 , 18 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Observa-se que o processo de trabalho da equipe de enfermagem nos Centros de Atenção Psicossocial Infanto-Juvenil (CAPSij) é marcado pelo descompasso entre o conhecimento teórico e a prática que realizam, referindo que o cuidado é prestado com base na perspectiva biológica, com enfoque em procedimentos técnicos e marcada pelo conhecimento de outro profissional, o qual aponta a ação a ser executada. 7 Outro desafio da enfermagem na ação de cuidar é a persistência da visão manicomial com saberes e práticas tradicionais que remontam estritamente aos cuidados básicos, à postura vigilante e punitiva, ao abandono e à violência praticada, pautados em uma estrutura central hospitalocêntrica com preconceitos e resistência para prestar assistência integral à saúde da criança e do adolescente com transtornos mentais, apresentando estoque de conhecimento intrínseco em saúde mental insuficiente assim como dificuldade de identificar e diferenciar os tipos de transtornos mentais. 6,8,9 De acordo com Schutz, define-se como estoque de conhecimento todas as memórias e vivências de um sujeito, elementos estes que são buscados diante do desconhecido.…”
Section: Introductionunclassified
“…Portanto, a enfermagem se faz presente no cuidado das crianças e adolescentes com transtornos mentais e tem importante papel que pode ser desempenhado no acompanhamento e na reabilitação psicossocial, sendo necessário apropriar-se de como cuidar e compreender como está sendo realizado o cuidado. 7 Na intenção de ampliar as perspectivas sobre o cuidado, essa pesquisa objetiva conhecer as percepções da equipe de enfermagem em face do cuidado de crianças e adolescentes com transtornos mentais internados nas unidades de internação de pediatria e psiquiatria de um hospital universitário do interior paulista.…”
Section: Introductionunclassified
“…It is observed that the work process of the nursing team in the Child and Youth Psychosocial Care Centers (CAPSij-in Portuguese) is marked by the mismatch between theoretical knowledge and the practice they perform, referring that the care is provided based on the biological perspective, focusing on technical procedures, and marked by the knowledge of another professional, who points out the action to be performed. 7 Another challenge of nursing in the action of care is the persistence of the asylum view with traditional knowledge and practices that go back strictly to basic care, the vigilant and punitive attitude, abandonment, and violence, based on a hospital-centered central structure with prejudice and resistance to provide comprehensive health care to children and adolescents with mental disorders, presenting an insufficient intrinsic stock of knowledge in mental health, as well as difficulty in identifying and differentiating the types of mental disorders. 6,8,9 According to Schutz, a stock of knowledge is defined as all the memories and experiences of a subject, elements that are sought when facing the unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nursing is present in the care of children and adolescents with mental disorders and has an important role that can be played in the follow-up and psychosocial rehabilitation, being necessary to understand how to care and to understand how the care is being provided. 7 With the intention of expanding the perspectives on care, this research aims to know the perceptions of the nursing staff regarding the care of children and adolescents with mental disorders hospitalized in the inpatient units of the pediatrics and psychiatry units of a university hospital in the interior of São Paulo.…”
Section: Introductionmentioning
confidence: 99%